Materialy k obosnovaniju predloženij po soveršenstvovaniju EVSK (na primere velosipednogo sporta i plavanija). Cast' I. Tendencii razvitija EVSK, vozrast i NTU vypolnenija i prisvoenija sportivnych zvanij i razrjadov - Kubeev, A. V.; Evtukh, A. V.; Mochalova, M. S.; Oganesyan, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In article results of discussion and the analysis of basic documents and materials of Uniform All-Russia sports classification (UASC) are presented. In connection with necessity of a scientific and methodical substantiation, and also with prospect of working out of version UASC on a forthcoming Olympic cycle (2019-2022), its basic sections and the components defining development of sports in the country are analysed. In a context of maintenance of solving progress in the given direction, the generalised model of development UASC on the basis of application of modern digital technologies of maintenance of information processes is offered.